PENINGKATAN MUTU PEMBELAJARAN QUR’AN HADITS MELALUI LITERASI DIGITAL - Wahidin; Abdul Halim Rais (CV. Lafadz Jaya, 2026)
This study aims to examine the influence of digital literacy on the learning of the Qur’an and Hadith and to identify the challenges and solutions in its implementation in madrasahs. The study employed a qualitative approach with a case study design conducted in five Islamic senior high schools in Kapuas Regency. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman model. The findings revealed that digital literacy significantly improves the quality of Qur’an and Hadith learning through the use of digital Qur’an applications, multimedia tafsir, and online learning platforms, making learning more interactive, flexible, and effective. Digital literacy also enhances students’ independent learning, critical thinking skills, and learning motivation. However, several challenges were identified, including limited teachers’ digital competence, inadequate technological infrastructure, and the lack of alignment between digital media and the madrasah curriculum. Therefore, continuous teacher training, the development of Islamic-based digital learning platforms, and the improvement of technological facilities are necessary to support innovative and relevant religious learning in the digital era.